The Littoral Benthos of the Apostle Islands National Lakeshore - Montz, Gary R. (University of Wisconsin-Stevens Point, College of Natural Resources, 1986)
The littoral benthos of the Apostle Islands National Lakeshore were sampled to provide baseline data on community composition and density. Samples were collected from 0.5, 1.5, 3.0, and 4.5m depths along 7 transects off five of the Apostle Islands: Basswood, Stockton, Cat, South Twin, and Rocky. A ponar grab sampler was used in soft substrates, and rocky substrates were samples using artificial substrate samplers (barbeque baskets filled with concrete spheres). Samples were collected every 4 weeks from 12 May to 26 October 1984. One hundred fifty four genera from 37 families were collected, and two major communities were found. Rock-rubble substrates had a fauna typical of lotic habitats and low densities (mean numbers/m2 = 226 +/- 25 (C.I. = .95), range = 34 - 723 organisms/m2). No taxon was predominant, and Trichoptera, Ephemeroptera,Chironomidae, and Mollusca composed the major proportion of the community. High oxygen levels and constant water movement, in the form of wave action, help explain the presence of lotic organisms. Soft substrates (bare sand, vegetated sand) had fauna characteristic of lentic habitats and higher densities (mean number/m2 3801 +/- 601 (C.I. = .95), range = 156 - 19,003 organisims/m2). Bare sand supported lower densities than vegetated areas. Chironomidae and Annelida (Oligochaeta) were predominant in these two substrates. Densities (numbers/m2) varied significantly (.05 level) with depth. Shallower depths and lower densities, with highest monthly mean densitieis found at the deeper sites. Exposure (determined subjectively) affected densitieis at the 3.0 and 4.5m sites, but was not significant at the 0.5 and 1.5m depths. The rock-rubble at the shallow depths may have provided more protection and interstitial refugia from turbulence, or exposure measures may have been inaccurate. Future studies should place multiple sampling transects directly in public use areas and compare the results with the baseline data provided by this study.